Thoracic Cavernous Lymphangioma Provoking Massive Chyloptysis - Robert Ferguson MD; Jeffrey Hodges MS; Cayce Harness-Brumley MD; Carlos Girod MD; Sonja Bartolome MD; J. Michael DiMaio MD (SAGE Publishing, 2013)
Chyloptysis is a relatively rare embodiment of disease that encompasses a lengthy differential and provides many diagnostic and therapeutic challenges. Presented here is the case of a young woman with massive chyloptysis due to a thoracic cavernous lymphangioma arising in the peripartum period. The severity of her condition mandated the use of cardiopulmonary bypass to resect her lymphangioma. We believe that the extent of her symptoms, etiology of disease, and surgical management represent a unique scenario in the literature.